ANALISIS HUBUNGAN ANTARA DINAMIKA PASANG SURUT DAN PERUBAHAN KUALITAS AIR DI MUARA BATANG ARAU: PERSPEKTIF KEBIJAKAN LINGKUNGAN - Rindang Kembar Sari; Wike Ayu Eka Putri; Aldri Frinaldi (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2026)
The Batang Arau Estuary is a strategic coastal area in Padang that serves as a vital transportation route, fishing zone, and economic hub. However, escalating anthropogenic activities-including domestic waste disposal and port operations-have led to the degradation of the estuarine water quality. This study aims to analyze the relationship between tidal dynamics and water quality fluctuations in the Batang Arau Estuary and to examine the subsequent implications for environmental management and policy. The research employed a quantitative descriptive method, collecting water samples from seven observation stations during both high and low tide conditions. The analyzed parameters included salinity, pH, temperature, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD5), and Chemical Oxygen Demand (COD). The results indicate that tidal fluctuations significantly influence the distribution of water quality parameters, particularly salinity and DO. Salinity values increased during high tide due to seawater intrusion, while lower values were observed during low tide as freshwater discharge became dominant. While pH and temperature generally remained within environmental standards, DO concentrations at several upstream stations fell below the threshold required to support aquatic life. Furthermore, COD concentrations at specific locations exceeded permissible limits, indicating organic pollution from domestic and port-related activities. To address these issues, integrated environmental management is essential. This includes pollution control, hydrodynamic-based monitoring, ecosystem rehabilitation, and the implementation of Integrated Coastal Zone Management (ICZM). Such measures are critical to ensuring the sustainability of the estuarine ecosystem and the long-term viability of coastal economic activities.